Direct Visualization of Single Nuclear Pore Complex Proteins Using Genetically‐Encoded Probes for DNA‐PAINT. Issue 37 (21st August 2019) - Schlichthaerle, Thomas; Strauss, Maximilian T.; Schueder, Florian; Auer, Alexander; Nijmeijer, Bianca; Kueblbeck, Moritz; Jimenez Sabinina, Vilma; Thevathasan, Jervis V.; Ries, Jonas; Ellenberg, Jan; Jungmann, Ralf
Abstract: The nuclear pore complex (NPC) is one of the largest and most complex protein assemblies in the cell and, among other functions, serves as the gatekeeper of nucleocytoplasmic transport. Unraveling its molecular architecture and functioning has been an active research topic for decades with recent cryogenic electron microscopy and super‐resolution studies advancing our understanding of the architecture of the NPC complex. However, the specific and direct visualization of single copies of NPC proteins is thus far elusive. Herein, we combine genetically‐encoded self‐labeling enzymes such as SNAP‐tag and HaloTag with DNA‐PAINT microscopy. We resolve single copies of nucleoporins in the human Y‐complex in three dimensions with a precision of circa 3 nm, enabling studies of multicomponent complexes on the level of single proteins in cells using optical fluorescence microscopy. Abstract : Genetically‐encoded self‐labeling enzymes such as SNAP‐tag and HaloTag are combined with DNA‐PAINT microscopy, enabling studies of multicomponent complexes on the level of single proteins in cells.